2008
DOI: 10.33585/cmy.60204
|View full text |Cite
|
Sign up to set email alerts
|

Gerronema nemorale (Basidiomycota, Agaricomycetes): anatomic-morphological, cultivational, enzymatic and molecular characteristics and its first records in the Republic of Korea.

Abstract: The basidiomycetous agaric Gerronema nemorale Har. Takah. was collected at several localities in the Republic of Korea (South Korea). A macro-and microscopic description and cultivational characteristics are given. Also physiological studies were performed. These included measuring of extracellular ligninolytic enzymes and monitoring of protein and glucose concentration in media. Its placement in the genus Gerronema in the recent sense is proven using molecular methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Phylogenetically, G. subclavatum and G. nemorale sequences grouped within the same clade when compared to other Gerronema species. These results are in aggreement with Antonín et al (2008) and Latha et al (2018), which shows that the ITS regions are conserved among G. subclavatum and G. nemorale . Our phylogenetic analysis also revealed that Omphalina and Gerronema species are only distantly related, which also supports previous findings by Moncalvo et al (2000).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Phylogenetically, G. subclavatum and G. nemorale sequences grouped within the same clade when compared to other Gerronema species. These results are in aggreement with Antonín et al (2008) and Latha et al (2018), which shows that the ITS regions are conserved among G. subclavatum and G. nemorale . Our phylogenetic analysis also revealed that Omphalina and Gerronema species are only distantly related, which also supports previous findings by Moncalvo et al (2000).…”
Section: Discussionsupporting
confidence: 87%
“…hixa , Laurus novocanariensis and Erica scoparia ssp. platycodon , on dead fallen twigs in lowland forests dominated by Pasania edulis Makino, Quercus myrsinaefolia Blume and Ligustrum japonicum Thunb., and on sapwood under the bark (Norvell et al 1994, Takahashi 2000, Banares et al 2006, Antonín et al 2008, Latha et al 2018). The studied sample Gerronema subclavatum was found on dead branches of Alnus orientalis L. Interestingly, G. nemorale Har.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malt extract agar and cherry decoction agar media were previously used to assay activity (Martin and Gilbertson 1976;Stalpers 1978); therefore, PDB and Kirk's medium were selected for this study. The laccase activity of the white rot fungus Gerronema nemorale examined under the same conditions was around 2-12 units/mL (Antonin et al 2008), while for S. latifolia the value was 0.05-0.04 units/mL. In G. nemorale, MnP and LiP activities were 0.01-0.3 units/mL and 0.1-0.8 units/mL, respectively, while the values in S. latifolia were found to be 0.001-0.035 units/mL for MnP and 1-11 units/mL for LiP activity.…”
Section: Discussionmentioning
confidence: 91%
“…Both Singer and Bigelow considered Gerronema to be pigment based and therefore emphasized pigmentation as a more important taxonomic character than other observed features ( Bigelow 1970 , 1982 , 1985 ; Singer 1986 ). Gerronema sensu Singer, however, was considered to be heterogeneous ( Clémençon 1982 ; Moser 1983 ; Kuyper 1986 ; Singer 1964 , 1975 , 1986 ; Norvell et al 1994 ; Antonín et al 2008 ), and Redhead (1986) restricted the genus to species having sarcodimitic tissues, a concept supported by Norvell et al (1994) . Along with Redhead, Norvell et al defined Gerronema as comprising lignicolous species with typical sarcodimitic tissues, and the genus was monophyletic according to this circumscription ( Redhead 1986 ; Norvell et al 1994 ).…”
Section: Introductionmentioning
confidence: 99%